Adaptation of Volvariella volvacea metabolism in high carbon to nitrogen ratio media. (1st April 2016) - Diamantopoulou, Panagiota; Papanikolaou, Seraphim; Aggelis, George; Philippoussis, Antonios
Highlights: High production of lipids and intracellular polysaccharides were observed at high glucose concentrations. Lipids and intracellular polysaccharides (%, w/w) were synthesized and then reconsumed. Linoleic was the predominate fatty acid of the produced cellular lipids. Phosphatidyl-choline and phosphatidyl-inositol were the major phospholipids. Glucose was the most abundant individual sugar of intracellular polysaccharides. Abstract: Increasing glucose concentration (up to 46%) in the culture medium of Volvariella volvacea resulted in a noticeable biomass increase (63.82%) and intracellular polysaccharide (IPS) production (32.84% in absolute and 51.34% in relative values). In high glucose concentrations, decreased biomass yields on glucose consumed were recorded. A non-negligible lipid was synthesized (up to 32.22%, w/w) in the first growth steps. Lipids and IPS were decreased as fermentation proceeded. Fatty acid composition of lipids was not remarkably affected by the C/N ratio imposed, whereas the concentration of neutral lipids increased in the high C/N ratio media. Phospholipid was the richest in saturated fatty acids lipid fraction. The major phospholipid classes, i.e. phosphatidyl-choline and phosphatidyl-inositol, were differentially affected by the high glucose concentrations, as the former increased its proportion and the latter decreased. Linoleic was the predominate fatty acid. C/N ratio and fermentation time affected IPS composition, as glucose increased in a high C/N ratio, while fructose and mannitol decreased.